The comparison of effectiveness, safety, and clinical outcome of one steppercutaneous abscess aspiration versus drainage by insertion of a drainage catheter in children with post-appendectomy abscess - Alireza Saeedi; Marjan Joodi; Siroos Nekoee; Meysam Izadi; Seyed Ali Alamdaran (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2018)
Introduction: Although radiologic guided abscess drainage with a drainage catheter has been a successful method for treatment of appendicular abscess after surgery, single stage aspiration technique could also be used as a good option in children with intra-abdominal abscess. The aim of this study was to compare efficacy, safety and clinical outcome of percutaneous abscess drainage versus aspiration in pediatric patients with post-appendectomy abscess formation. Materials and Methods: This randomized control trial was conducted under the supervision of Mashhad University of medical sciences. Children were enrolled in the study with suspicion of post-appendectomy abscess formation. Patients were divided into two groups (drainage or aspiration) with simple sampling method. Demographic characteristics and clinical outcome were compared between the two groups. Data analysis was done using SPSS version 16. Results: Fifty children with post-appendectomy abscess were enrolled in this study. Their mean age was 10.4 ± 4.1 year (range from 5 to 19yrs). Drainage was successful in 88% of patients and the succeed rate in aspiration group was 96% and this difference was not significant statistically (p=0.609). Duration of hospital stay was longer in the drainage group in comparison with aspiration (2.8 ± 0.55 vs. 2.1 ± 0.47, p-value < 0.001). Conclusion: Efficacy, safety and other clinical outcomes of percutaneous abscess drainage and aspiration were the same in pediatric patients with smaller than 5 cm post-appendectomy abscess. Due to lower cost and parental satisfaction, aspiration would be a good choice in children with small post-appendectomy abscess.